2008
DOI: 10.1074/jbc.m800498200
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Regulation of Fc Receptor γ-Chain Gene Expression by Multiple Transcription Factors, Including Sp1, GABP, and Elf-1

Abstract: The Fc receptor ␥-chain (FcR␥), which was first identified as a constituent of the high affinity IgE receptor, associates with various cell surface receptors to mediate intracellular signals. We identified three transcriptional enhancer elements in the 5 region of the human FcR␥ gene; one of the cis-elements was recognized by the transcription factor Sp-1 and another was recognized by GABP or Elf-1. The sequence of the other element was similar to a binding motif of the C/EBP family. Overexpression experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
(21 reference statements)
2
15
0
Order By: Relevance
“…The interaction of Ets family transcription factors with Sp1 has been shown to synergistically trans-activate many genes including human CD18 [14], Tenascin-C [21], Fc receptor γ-chain [22], and interleukin-12 p40 [23]. In the mouse sell promoter, an Sp1 binding site overlaps with an Ets1 binding site.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of Ets family transcription factors with Sp1 has been shown to synergistically trans-activate many genes including human CD18 [14], Tenascin-C [21], Fc receptor γ-chain [22], and interleukin-12 p40 [23]. In the mouse sell promoter, an Sp1 binding site overlaps with an Ets1 binding site.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that mTERF and TWINKLE mRNAs decrease similarly and yet mTERF promoter only contains two tandemly arranged sites that bind with high affinity two ␣/␤ NRF-2 monomers indicates a lack of correlation between the extent of mRNA level decrease and the number and arrangement of NRF-2 sites. It is notable that the TWINKLE promoter contains, in close proximity of the Ϫ45 NRF-2 site, a sequence recognized by Sp1, a factor that is known to physically and functionally interact with NRF-2 on several promoters (8,31). …”
Section: Discussionmentioning
confidence: 99%
“…The most plausible candidate target genes are TPD52 (MIM: 604068), which is involved in B cell maturation; 6 PAG1 (MIM: 605767), involved in T and B cell activation; 7-10 and ZBTB10, a putative repressor of the Sp1 transcription factor (TF), 11 which regulates multiple immune-related genes. 12,13 We first considered the possibility that the lack of a published association between rs7009110 and the expression of nearby genes could represent a false-negative finding, arising because (1) a true association did not exceed the false discovery rate threshold in the original eQTL studies and so was not reported; and/or (2) most published eQTL studies surveyed used expression microarrays, which have incomplete coverage of gene expression patterns. To test this possibility, we analyzed RNA-seq data obtained by the Geuvadis Project 14 for lymphoblastoid cell line (LCL) samples of 373 individuals of European descent from the 1000 Genomes Project.…”
mentioning
confidence: 99%